(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Atrial fibrillation (AF) is one of the most pressing problems in cardiology, due to the widespread prevalence of this arrhythmia [5] and the severity of complications associated with it, among which the most unfavorable are the development of strokes [8,11] and heart failure [1, 6].